WhatsApp communication service - Mrad, Mona (2022)
The purpose of this study is to explore the pros and cons of WhatsApp communication service and its likely effects on consumer behavior and one’s perception of luxury brands. Design/methodology/approach This study conducted 27 in-depth interviews with UK-based participants. This study used NVivo12 to thematically analyze the collected data. Findings The findings indicate that perceived communication convenience, searching for prepurchase information, intimate consumer–brand relationship, perceived self-worth and the thrill of a new service positively contribute to luxury customers’ acceptance of WhatsApp communication usage. Nevertheless, many factors including push promotional strategy, poor service quality, brand “massification” effect, deficient sensory experience, fear of financial risk and deceptive practices, all curbed the participants’ acceptance of this communication platform. When service is poor, all these factors jeopardized the luxury image, causing an impaired brand image, accompanied with negative word of mouth and in some instances, unexpected anticonsumption reactions. Research limitations/implications This study carries the limitations of any exploratory and qualitative research. Therefore, future research should replicate this study in other areas and for other instant messaging platforms. Practical implications The implications of this study serve as a reference for luxury brands’ managers when managing their WhatsApp service. This study provides important insights into the risk of using WhatsApp by luxury brands to communicate with customers. The overall conclusion is that WhatsApp communication service requires a close, supervised and innovative use to benefit luxury brands. Originality/value To the best of the authors’ knowledge, the topic of WhatsApp usage as a communication mean in the luxury industry is still largely underexplored, hence filling a gap in the literature that needs to be addressed given its significant implications.